2009
DOI: 10.2174/1874318800903010009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Chicken Embryo-Adapted H9N2 Subtype Avian Influenza Virus

Abstract: The low pathogenic avian influenza (LPAI) caused by H9N2 virus has generated economic losses in the Korean poultry industry since 1999, but field isolates could not be used for killed oil emulsion vaccine directly because of low productivity in embryonated chicken eggs (ECE). Therefore, we established a vaccine strain, KBNP-0028, by passage through ECE with allantoic fluid showing the highest volume and titer. KBNP-0028 possessed 158 N-glycan on hemagglutinin (HA) as its parent strain, but acquired a 16 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In Korea, nationwide occurrences of LPAI caused by AIV H9N2 have been reported since the first outbreak of the disease in 1996 and have caused mild disease with up to 30% mortality in broiler breeder flocks [22]. To date, the disease has increased and has become endemic [21,23]. Under certain conditions, Korean isolates have evolved causing 30% mortality and a severe decrease in egg production in layers that were experimentally infected [19].…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, nationwide occurrences of LPAI caused by AIV H9N2 have been reported since the first outbreak of the disease in 1996 and have caused mild disease with up to 30% mortality in broiler breeder flocks [22]. To date, the disease has increased and has become endemic [21,23]. Under certain conditions, Korean isolates have evolved causing 30% mortality and a severe decrease in egg production in layers that were experimentally infected [19].…”
Section: Discussionmentioning
confidence: 99%
“…HA and NA genomes of recombinant H5N6 virus were synthesized in the sequence most frequent among clade 2.3.4.4c H5N6 isolates during the years 2014–2016 ( n = 73) (Cosmo Genetech, Seoul, Korea), with a change in cleavage site from a polybasic amino acid (RERRKR) site to the monobasic amino acid (ASGR) site of the Korean H9N2 LPAI virus, A/chicken/Korea/KBNP- 0028 /00( H9N2 ) ( 0028 ) [ 24 ]. Internal genes of PR8, LPAIV H9N2 01310, 0028 and LPAI A/wild duck/Korea/SNU50-5/2009(H5N1) (SNU50-5) were used to generate recombinant H5N6 strains possessing internal proteins of PR8 or avian IAVs (Influenza A viruses) [ 12 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…For genetic analysis of HA gene of H9N2, the HA cleavage site contains single basic amino acids 'SRSSR' which known as the characteristics of low pathogenic avian influenza. It has been reported that the numbers of basic amino acid at the HA cleavage site may affect the pathogenesis of influenza virus due to the HA protein has to be cleaved by cellular protease enzyme of the host (Kwon et al, 2009). In this study, the H9N2 virus harbored 155-Threonine (T), 183-asparagine (N) and 226-Leucine (L) amino acids at receptor binding site indicating human specific receptor binding site.…”
Section: Genetic Analysis Of Internal Genes Of H5n1 Virusesmentioning
confidence: 84%